Penyusunan Rencana Anggaran Biaya Pembangunan Irigasi Desa Penataran, Jawa Timur - Ferenia Safura; Anggie Ria Paulina Purba (STIKes Ibnu Sina Ajibarang, 2025)
Growth and development in the village has an influence on the hydrological cycle that impacts the irrigation channel system in Penataran Village, Nglegok Subdistrict, Blitar District, East Java. Irrigation has an important role in the lives of mainly rural communities, so the government needs to make policies for irrigation development to improve the function of irrigation in accordance with the policies that must be followed. Preparation of a Cost Budget Plan (RAB) is an activity in a project to calculate the estimated cost budget required in the construction of a project and with these costs the construction of the project can be carried out in accordance with the composition of the Cost Budget Plan (RAB). The method used in the preparation is the unit price method. The results of the activity show that irrigation development costs Rp. 99,017,500.